Safety, tolerability, acceptability and immunogenicity of an influenza vaccine delivered to human skin by a novel high-density microprojection array patch (Nanopatch™). Issue 26 (18th June 2018) - Fernando, Germain J.P.; Hickling, Julian; Jayashi Flores, Cesar M.; Griffin, Paul; Anderson, Christopher D.; Skinner, S. Rachel; Davies, Cristyn; Witham, Katey; Pryor, Melinda; Bodle, Jesse; Rockman, Steve; Frazer, Ian H.; et al.
Abstract: Background: Injection using needle and syringe (N&S) is the most widely used method for vaccination, but requires trained healthcare workers. Fear of needles, risk of needle-stick injury, and the need to reconstitute lyophilised vaccines, are also drawbacks. The Nanopatch (NP) is a microarray skin patch comprised of a high-density array of microprojections dry-coated with vaccine that is being developed to address these shortcomings. Here we report a randomised, partly-blinded, placebo-controlled trial that represents the first use in humans of the NP to deliver a vaccine. Methods: Healthy volunteers were vaccinated once with one of the following: (1) NPs coated with split inactivated influenza virus (A/California/07/2009 [H1N1], 15 µg haemagglutinin (HA) per dose), applied to the volar forearm (NP-HA/FA), n = 15; (2) NPs coated with split inactivated influenza virus (A/California/07/2009 [H1N1], 15 µg HA per dose), applied to the upper arm (NP-HA/UA), n = 15; (3) Fluvax® 2016 containing 15 µg of the same H1N1 HA antigen injected intramuscularly (IM) into the deltoid (IM-HA/D), n = 15; (4) NPs coated with excipients only, applied to the volar forearm (NP-placebo/FA), n = 5; (5) NPs coated with excipients only applied to the upper arm (NP-placebo/UA), n = 5; or (6) Saline injected IM into the deltoid (IM-placebo/D), n = 5. Antibody responses at days 0, 7, and 21 were measured by haemagglutination inhibition (HAI) and microneutralisation (MN) assays. Findings: NP vaccination was safe and acceptable; all adverse events were mild or moderate. Most subjects (55%) receiving patch vaccinations (HA or placebo) preferred the NP compared with their past experience of IM injection with N&S (preferred by 24%). The antigen-vaccinated groups had statistically higher HAI titres at day 7 and 21 compared with baseline (p < 0.0001), with no statistical differences between the treatment groups (p > 0.05), although the group sizes were small. The geometric mean HAI titres at day 21 for the NP-HA/FA, NP-HA/UA and IM-HA/D groups were: 335 (189–593 95% CI), 160 (74–345 95% CI), and 221 (129–380 95% CI) respectively. A similar pattern of responses was seen with the MN assays. Application site reactions were mild or moderate, and more marked with the influenza vaccine NPs than with the placebo or IM injection. Interpretation: Influenza vaccination using the NP appeared to be safe, and acceptable in this first time in humans study, and induced similar immune responses to vaccination by IM injection.